The Effect of Time Budget Pressure, Work Stress, and Independence on Auditor Performance - Yosua Viera; Adam Zakaria; Ati Sumiati (Journal of International Conference Proceedings, 2021)
This research was conducted to obtain empirical evidence regarding the Effect of Time Budget Pressure, Work Stress, and Independence on Auditor Performance. This study uses primary data with a sample of auditors working at the Public Accounting Firm (KAP) in Bekasi where listed in Directory Institut Akuntan Publik Indonesia (IAPI) period of 2021. The sampling technique in this study used convenience sampling with 50 respondents. Hypothesis testing in this study using multiple regression models using SPSS 25. Based on the results of the analysis in this study, it can be concluded that: (1) time budget pressure has a significant positive effect on auditor performance, (2) work stress has a significant positive effect on auditor performance, and (3) independence has a significant positive effect on performance. auditors. Thus, the increasing of each of the variables of time budget pressure, work stress, and independence, each of these independent variables will be able to improve the performance of the auditor.